2007
DOI: 10.1515/cclm.2007.316
|View full text |Cite
|
Sign up to set email alerts
|

Altered angiogenesis in preeclampsia: evaluation of a new test system for measuring placental growth factor

Abstract: Our results support the hypothesis that an imbalance between factors promoting angiogenesis, such as PLGF, and factors antagonizing angiogenesis, such as sFLT-1, has a fundamental role in the pathogenesis of preeclampsia. The new established ELISA test can be considered reliable and it offers many advantages. As it is authorized for routine diagnostic testing, it may offer new possibilities in the prediction of preeclampsia in clinical routine.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
8
0

Year Published

2009
2009
2014
2014

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 8 publications
(9 citation statements)
references
References 38 publications
1
8
0
Order By: Relevance
“…[6][7][8][9] Reduced PlGF levels have been suggested to be a result of inadequate placental production, 12 which has been previously reported. 7,32 Qazi et al 33 have examined the circulating levels of VEGF and sFlt-1 and suggested that decreased VEGF levels resulting from elevated sFlt-1 might be a potential cause of the pathogenesis of preeclampsia.…”
Section: Discussionmentioning
confidence: 99%
“…[6][7][8][9] Reduced PlGF levels have been suggested to be a result of inadequate placental production, 12 which has been previously reported. 7,32 Qazi et al 33 have examined the circulating levels of VEGF and sFlt-1 and suggested that decreased VEGF levels resulting from elevated sFlt-1 might be a potential cause of the pathogenesis of preeclampsia.…”
Section: Discussionmentioning
confidence: 99%
“…We have recently demonstrated that the PLGF concentrations in normal pregnancies show a steady increase starting at 15 weeks of pregnancy with a peak at 28-32 weeks and a consistent decline thereafter. PLGF serum levels of patients with preeclampsia are significantly lower than the levels in nonpreeclamptic pregnancies [16] . At present, the women at risk of preeclampsia are identified on the basis of epidemiological, clinical and anamnestic risk factors.…”
Section: Introductionmentioning
confidence: 68%
“…From the beginning of the second trimester at 15 weeks of pregnancy, PLGF concentrations showed a steady increase until 30-32 weeks [16] . Our study depicts the expression of PLGF between 15 and 18 weeks of pregnancy in patients joining our clinic for invasive prenatal diagnostics.…”
Section: Commentmentioning
confidence: 98%
See 2 more Smart Citations